4 Prognostic impact of tumor infiltrating natural killer cells in ovarian carcinoma. (18th September 2019) - Henriksen, J; Donskov, F; Waldstrøm, M; Jakobsen, A; Dahl Steffensen, K
Abstract : Objectives: Whereas the prognostic impact of infiltrating T cells in ovarian cancer is established, the impact of other immune cells is largely unknown. The aim of the present study was to investigate the prognostic impact of intratumoral T cells, Natural Killer (NK) cells, neutrophils and PD-L1 expression. Methods: All patients diagnosed with high-grade serous carcinoma (HGSC) in Denmark in 2005 were included in the study (N=283). Immunohistochemical staining with antibodies for PD-L1, T cells (CD8), neutrophils (CD66b), and NK cells (CD57) were performed. Cell densities were analyzed using a digital image analysis method. The primary endpoint was overall survival (OS). Results: In patients with high levels of tumor infiltrating NK-cells the median OS was 45 vs 29 months (figure 1 ). The median OS was 37 vs 25 months (p=0.0008) for high vs low level of tumor infiltrating T cells, respectively. In multivariate analysis high numbers of NK-cells and T-cells remained independent markers of favorable OS with hazard ratios of 0.72 (p= 0.020) and 0.67 (p=0.041) in favor of high T cell and high NK cell density respectively. A high level of PD-L1 expression was associated with improved OS (37 months vs 22 months, p=0.0006). PD-L1 was only borderline significant in the multivariate analysis (HR 0.77, p=0.061). Neutrophils had no significant association with OS. Conclusions: This population based cohort study demonstrated a favorable prognostic impact of high levels of tumor infiltrating NK-cells in patients with HGSC, and confirmed the importance of tumor infiltrating T cells. This may influence the future development of immunotherapy in ovarian carcinoma.